Measurement of electroweak parameters from hadronic and leptonic decays of the Z0 - Dova, María Teresa (1991)
We have studied the reactions e+e−→hadrons, e+e−, μ+ μ− and τ+τ−, in the energy range 88.2 ≦ √s ≦ 94.2 GeV. A total luminosity of 5.5 pb−1, corresponding to approximately 115000 hadronic and 10000 leptonic Z0 decays, has been recorded with the L3 detector. From a simultaneous fit to all of our measured cross section data, we obtain assuming lepton universality: Mz = 91.181 ± 0.010 ± 0.02 (LEP) GeV, Γz = 2501 ± 17 MeV, Γhad= 1742 ± 19 MeV, Γt = 83.6 ± 0.8 MeV. If we do not assume lepton universality, we obtain for the partial decay widths of the Z0 into e+e−, μ+μ− and τ+ τ−: Γe = 83.3 ± 1.1 MeV, Γμ = 84.5 ± 2.0 MeV, Γτ = 84.0 ± 2.7 MeV. From the measured ratio of the invisible and the leptonic decay widths of the Z0, we determine the number of light neutrino species to be Nv =3.05±0.10. We include our measurements of the forward-backward asymmetry for the leptonic channels in a fit to determine the vector and axial-vector neutral current coupling constants of charged leptons to the Z0. We obtain g¯V = −0.046+0.015−0.012 and g¯A = −0.500 ± 0.003. In the framework of the Standard Model, we estimate the top quark mass to be mt =193+52−69 ± 16 (Higgs) GeV, and we derive a value for the weak mixing angle of sin2θW ≡ 1 − (MW/MZ)2 = 0.222 ± 0.008, corresponding to an effective weak mixing angle of sin2θ¯W = 0.2315 ± 0.0025.